1997
DOI: 10.7863/jum.1997.16.9.609
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydramnios and fetal intrauterine growth restriction: ominous combination.

Abstract: The purpose of this study was to evaluate the significance of polyhydramnios combined with intrauterine growth restriction. During a 6 year period, 39 fetuses were identified by prenatal sonography as having both polyhydramnios and intrauterine growth restriction. Polyhydramnios was defined as a four‐quadrant amniotic fluid index of 24 or greater (mean 30.5, range 24 to 40). Intrauterine growth restriction was defined as estimated fetal weight less than the tenth percentile (Hadlock standards). The mean birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
3
37
2
Order By: Relevance
“…One report presented 22.2% chromosome abnormalities among women with polyhydramnios (Zahn et al 1993). Another report presented 38.5% chromosome abnormalities among women with polyhydramnios together with fetal growth restriction (Sickler et al 1997). These frequencies in Western countries are comparable to our results in the Japanese population.…”
Section: Discussionsupporting
confidence: 90%
“…One report presented 22.2% chromosome abnormalities among women with polyhydramnios (Zahn et al 1993). Another report presented 38.5% chromosome abnormalities among women with polyhydramnios together with fetal growth restriction (Sickler et al 1997). These frequencies in Western countries are comparable to our results in the Japanese population.…”
Section: Discussionsupporting
confidence: 90%
“…Some of these ®ndings include: intrauterine growth retardation (IUGR) (Salihu et al, 1997;Nyberg et al, 1993;Twining et al, 1993); abnormal growth, as measured by the biparietal diameter and femur length ratio (Benattar et al, 1999); Seoud et al, 1994;Dicke and Crane, 1991;(Ginsberg et al, 1990); choroid plexus cysts (Reinsch, 1997;Donnenfeld, 1995;Nadel et al, 1992;Platt et al, 1991;Fitzsimmons et al, 1989;Ostlere et al, 1989;Chitkara et al, 1988); abnormal positioning of ®ngers and clenched hand (Quintero et al, 1999); cardiac abnormalities (Gembruch et al, 1997;Paladini et al, 1993;Wladimiroff et al, 1989); echogenic bowel (Sipes et al, 1994;Scioscia et al, 1992); and facial and head abnormalities (Nicolaides et al, 1992a(Nicolaides et al, ,b,1993Benacerraf et al, 1986). Other unusual ®ndings with more uncertain implications include cystic hygroma (Shields et al, 1998); nuchal thickening (Nyberg et al, 1993); single umbilical artery (Sener et al, 1997); and polyhydramnios (Sickler et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our study inclusion criteria required the combination of severe IUGR and oligohydramnios which, when seen together in combination with an abnormal flow in the umbilical artery, may implicate the presence of thrombophilia. Notably, Sickler et al 18 showed that early IUGR associated with polyhydramnios was a very strong predictor for major anomalies and aneuploidy.…”
Section: Discussionmentioning
confidence: 99%